2D Seismic Interpretation to Understand the Structural Geometry of Cretaceous Sand Packages, Jabo Field, Pakistan - Khan, M. J.; Umar, M.; Khan, M.; Das, A. (The Nucleus, 2019)
This study is focused on interpretation of 2D seismic reflection profiles coupled with borehole logs of Jabo Field (JF). The seismic interpretation revealed the configuration of basin fill deposits, subsurface geological structural geometries and their association with tectonic interventions in JF, Lower Indus Basin, Pakistan. Primarily, the tectonic stresses control the dimensions, geometry and style of deformation of geological structures which contribute in development of hydrocarbon trapping system. We have studied the structural geometries of Cretaceous sand packages which serve as a reservoir in oil & gas prone JF. Isochron and isopach maps were prepared to delineate the geological structure of Top of Lower Goru (TLG), Top of Middle Sand (TMDS) and Top of Basal Sand (TBSL). TLG forms a three-way dip closure bounded by a NE-SW trending major fault of the JF; the geological structure at TMDS level is a two-way fault bounded since to the north and south it is bounded by dipping blocks; and the structural closure at TBSL level is two-way dip and two-way faults bounded. The structural closure to the north and south provided by the dipping horizons, from west by Main Fault Line (MFL) of JF and from east the closure is provided both by Secondary Fault Line (SFL) of the JF and dipping surfaces of sand packages. Interpretation shows the geological implications of extensional regime in the study area, dominated by horst and graben structures which are believed to be promising hydrocarbon traps.